Purse seine productivity in Lhok Pawoh fishing port, Sawang, South Aceh. Issue 1 (February 2021) - Rahmah, A; Ulfa, M; Damora, A; Aprilla, R M; Chaliluddin, M
Abstract: The capability of catching from fishing gear can be known from the fishing productivity. The purpose of this study was to calculate the productivity of purse seine vessels in the Fishing Port of Lhok Pawoh, Sawang, South Aceh. This research was conducted from June 10 th to July 10 th 2019. The method used was a census method by collecting some data such as number of fishing trip (during 2018), species and number of catches, and specification of 15 units of purse seine at Lhok Pawoh fishing port, then the data was analyzed descriptively. The results showed that the material of purse seiner at Lhok Pawoh were made of local wood with a vessel size of 23-60 GT, LOA was 16-24.2 meters, breadth was 4-7.5 meters, depth was 1.3-1.9 meters, and main engine power was 90-360 HP. The purse seine at PPI Lhok Pawoh has a length of between 1, 100-1, 500 meters and a width of 45-100 meters with the number of fishermen ranges between 18-28 people/unit. The total catches of purse seine during the research was 162, 116 kg, dominated by skipjack tuna (67.97%). The highest productivity (production/GT) for large pelagic target was 2, 458.8 kg/GT, and the lowest one was 209.3 kg/GT. The highest productivity (production/GT) for small pelagic target was 2, 630.7 kg/GT and the lowest one was 418.3 kg/GT. The highest productivity (production/trip) for large pelagic target was 3, 046.0 kg/trip, and the lowest one was 187.6 kg/trip. The highest productivity (production/trip) for small pelagic target was 2, 067.3 kg/trip and the lowest one was 340.2 kg/trip.